6(x-6)-8(x-2)=-16

Simple and best practice solution for 6(x-6)-8(x-2)=-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-6)-8(x-2)=-16 equation:


Simplifying
6(x + -6) + -8(x + -2) = -16

Reorder the terms:
6(-6 + x) + -8(x + -2) = -16
(-6 * 6 + x * 6) + -8(x + -2) = -16
(-36 + 6x) + -8(x + -2) = -16

Reorder the terms:
-36 + 6x + -8(-2 + x) = -16
-36 + 6x + (-2 * -8 + x * -8) = -16
-36 + 6x + (16 + -8x) = -16

Reorder the terms:
-36 + 16 + 6x + -8x = -16

Combine like terms: -36 + 16 = -20
-20 + 6x + -8x = -16

Combine like terms: 6x + -8x = -2x
-20 + -2x = -16

Solving
-20 + -2x = -16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + -2x = -16 + 20

Combine like terms: -20 + 20 = 0
0 + -2x = -16 + 20
-2x = -16 + 20

Combine like terms: -16 + 20 = 4
-2x = 4

Divide each side by '-2'.
x = -2

Simplifying
x = -2

See similar equations:

| 3x+18=10x-15 | | (x+2)+(x+4)=20+x | | 3K-6=-9 | | 5w-12=63 | | 6(2z-1)-2(7+3)=5(z+1) | | 9(v+2)-3v=3(2v+1)-8 | | 7(4-t)+3=-3(t-3)-6 | | y=7.5X+10 | | 10(a+1)-14a=9-(4a+1) | | 8(x-9)-4=-76 | | -8(2t^2+8t-6)=0 | | 5/7x-7=53 | | A+(-35)=-75 | | 25x-4=40x+2 | | -6.75+2.25x=x | | 9(x-2)+8=4x+5(-2+x) | | 6[3-(-8x-2)]=240x+78 | | 3(x-2)=5(x-3)+2 | | A+(-35)=75 | | 6(3n-1)+9=3(6n+3) | | 2x+4-7(x+1)=3x+4 | | 4y^2+x=0 | | -23/24=11/12+5x/6 | | 2.5x-8.8=-14.8+1.5x | | 5+35x=15x+53 | | 4b=30 | | -2y-17-22=2y+3y(y-6) | | 12+3x/5=39 | | 17000=-0.75x^2+255x-1000 | | x^2-8=4x+4 | | 3a^2-13a=10 | | 72.00+x=79.84 |

Equations solver categories